Legalitas Eksekusi Terhadap Objek Jaminan Fidusia Yang Dialihkan Pihak Konsumen Tanpa Sepengetahuan Pihak Leasing - Rindi Mariana Antika; Mutia CH. Thalib; Mohammad Taufiq Zulfikar Sarson (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2023)
asically the execution of fiduciary guarantee objects has been regulated in Law Number 42 of 1999 concerning Fiduciary Guarantees, specifically the procedure for executing fiduciary guarantee objects. Fiduciary collateral objects in the form of movable objects that are transferred by consumers (fiduciary givers) to third parties without the knowledge of the leasing party (fiduciary recipients) are an unlawful act, thus causing losses to fiduciary recipients. Based on Article 23 paragraph (2) UUJF, the fiduciary giver is prohibited from transferring, pawning, or renting to other parties objects that are objects of fiduciary guarantees that are not inventory objects, except with prior written approval from the fiduciary recipient. Conceptually, fiduciary guarantees are a form of legal relationship based on trust. Trust in this case is that the fiduciary recipient believes in giving part of the property rights to the fiduciary giver, until the fiduciary giver completes the installments of the object. So the fiduciary recipient still has the right to the object, which if one day the fiduciary giver breaks his promise, commits an unlawful act and there is no good faith, the fiduciary recipient can execute the fiduciary guarantee object.